In vitro genotoxic and cytotoxic effects of doxepin and escitalopram on human peripheral lymphocytes. (3rd April 2018) - Cobanoglu, Hayal; Coskun, Mahmut; Çayir, Akin; Coskun, Munevver
Abstract: Antidepressants are drugs used for the treatment of many psychiatric conditions including depression. There are findings suggesting that these drugs might have genotoxic, carcinogenic, and/or mutagenic effects. Therefore, the present in vitro study is intended to investigate potential genotoxic and cytotoxic effects of the antidepressants escitalopram (selective serotonin reuptake inhibitor) and doxepin (Tricyclic antidepressant) on human peripheral lymphocytes cytokinesis-block micronucleus (CBMN), sister chromatid exchange (SCE), and single cell gel electrophoresis (alkaline comet assay) were used for the purpose of the study. In the study, four different concentrations of both drugs (1, 2.5, 5, and 10 µg/mL) were administered to human peripheral lymphocytes for 24 h. The tested concentrations of both drugs were found to exhibit no cytotoxic and mitotic inhibitory effects. SCE increase caused by 5 and 10 µg/mL of escitalopram was found statistically significant, while no statistically significant increase was observed in DNA damage and micronucleus (MN) formation. Moreover, the increase caused by doxepin in MN formation was not found statistically significant. Besides, 10 µg/mL of doxepin was demonstrated to significantly increase arbitrary unit and SCE formation. These findings suggest that the investigated concentrations of escitalopram and doxepin were non-cytotoxic but potentially genotoxic at higher concentrations.